Systematic Literature Review: Pemantauan Beban Latihan Internal dan Kejadian Cedera pada Pemain Sepak Bola Elit - Qintarazany Elhaqe; Muhamad Fahmi Hasan; Mia Riko; Gifran Rihla Gifarka Latief; Agung Dwi Juniarsyah; Rini Syafriani; Tommy Apriantono (Indonesian Journal of Kinanthropology (IJOK), 2025)
Background: Football training is frequently associated with the injuries occuring, thus highlighting the crucial need for sports science to focus on the relationship between training load and injury incidence. In team sports, injuries can disrupt both individual athlete performance and overall team success. Training-load-related injuries are generally preventable, necessitating practical approaches such as internal training load monitoring. Methods: This study employed a systematic literature review methodology. Relevant keywords were combined using the Scopus database. Only English-language research articles published between 2014 and 2024, focusing on internal training load monitoring and injury in football, and involving professional or elite male and female football players, were analyzed. Results: The analysis yielded seven research articles that met the inclusion criteria. Injuries in football are a significant concern due to their negative impact on team. A significant relationship between internal load measurements and injury occurrence was found, although some previous studies did not support this finding. Internal training load variables applicable to football include Rate of Perceived Exertion (RPE), heart rate, and blood biomarkers. Conclusions: A significant relationship exists between internal load measurements and injury occurrence in elite football players. In the context of training load monitoring, there is a significant practical value for coaches and healthcare staff to adopt this approach as an injury prevention strategy. For professional or elite level football, particularly, it is recommended to integrate monitoring methods using multiple internal load measurement variables.